The Democracy of Objects - Bryant, Levi R. (New Metaphysics, 2011)
In The Democracy of Objects Bryant proposes that we break with the epistemological tradition and once again initiate the project of ontology as first philosophy. Bryant develops a realist ontology, called -onticology-, which argues that being is composed entirely of objects, properties, and relations. Bryant proposes that objects are dynamic systems that relate to the world under conditions of operational closure.